2011
DOI: 10.1007/s00405-011-1789-2
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of bacteremia and amount of bleeding during septoplasty

Abstract: The aim of this study was to investigate the relationship between the amount of bleeding and bacteremia during nasal septal surgery. Seventy-one patients undergoing septoplasty were enrolled in the present study. The amount of bleeding was measured and recorded for each patient. Preoperative and postoperative blood cultures were collected immediately after the induction of anesthesia and 20 min after the operation, respectively. While none of the blood cultures taken preoperatively were positive for any organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Finally, an interesting relationship was observed by Koc et al [11] between the amount of bleeding during septoplasty and subsequent bacteremia. Bacteremia was detected in 9 patients out of 71 who underwent septoplasty and it was more frequently encountered among those patients with a greater amount of bleeding during surgery.…”
Section: Effectiveness Of Antibiotic Therapy In Septoplastymentioning
confidence: 79%
“…Finally, an interesting relationship was observed by Koc et al [11] between the amount of bleeding during septoplasty and subsequent bacteremia. Bacteremia was detected in 9 patients out of 71 who underwent septoplasty and it was more frequently encountered among those patients with a greater amount of bleeding during surgery.…”
Section: Effectiveness Of Antibiotic Therapy In Septoplastymentioning
confidence: 79%
“…Koç et al [5,13], evaluated the relationship between bacteremia and amount of bleeding during septoplasty and tonsillectomy. They reported that bacteremia was more frequently encountered among those with a greater amount of bleeding during the both surgery.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus bacteremia appears to be of endogenous origin since the bacteria originate from colonies in the nasal mucosa [ 13 ]. Actually bacteremia was more frequently encountered among those with a greater amount of bleeding during the nasal surgery by Koc et al [ 8 ]. Patients with bleeding have an increased risk of developing bacteremia that could produce systemic complications, and Perl [ 20 ] described advances in the prevention of S. aureus infections from endogenous colonization in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Routine antibiotic prophylaxis was found to be redundant because the infection rate after elective nasal surgery (e.g. corrective rhinoplasty) was very low according to the review of Koc et al [ 8 ]. However, patients with nasal bone fracture who had external wounds on their nose had an increased risk of infection compared with corrective rhinoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation